Promoting national and household food security in Bangladesh: Evolving roles of public stocks, cereal distribution and private trade - Dorosh, Paul A. (University Press Limited, 2021)
Large-scale government interventions in cereal markets supported by public stocks have been a central part of food in the Indian sub-content since the days of British colonial India. Following the Great Bengal Famine of 1943, during which an estimated three million people died of hungerrelated causes, the colonial government instituted a system of government sales and distribution of cereals designed to help ensure minimum food consumption for poor households (Sen 1982). Public distribution systems continued in both India and Pakistan following independence in 1947. The famine conditions in 1972-74 that followed the liberation war and Bangladesh’s independence in December 1971 strongly reinforced the perceived need for major public interventions to ensure food security (see Ahmed, Haggblade, and Chowdhury 2000).